Enzymatic C-demethylation of 1-[2-(5-tert-butyl-[1,3,4]oxadiazole-2-carbonyl)-4-fluoro-pyrrolidin-1-y l]-2-(2-hydroxy-1,1-dimethyl-ethylamino)ethanone(LC15-0133) in rat liver microsomes - Yoo, Hye Hyun; Chung, Hye Jin; Lee, Jaeick; Lee, Chang-Seok; Kang, Min Jung; Kim, Dong-Hyun (AMER SOC PHARMACOLOGY EXPERIMENTAL THERAPEUTICS, 2008)
The in vitro metabolism of 1-[2-(5-tert-butyl-[1,3,4] oxadiazole-2-carbonyl)-4-fluoro-pyrrolidin-1-yl]-2-(2-hydroxy-1,1-dimethyl-ethylamino)-ethanone(LC15-0133), a novel dipeptidyl peptidase-4 inhibitor, was investigated using a hepatic microsomal system. The structures of the metabolites were characterized using mass spectral analysis and by comparison with synthetic references. The in vitro incubation of LC15-0133 with rat liver microsomes resulted in the formation of six metabolites, with the major metabolic reactions being hydroxylation and carbonyl reduction. Of the metabolites, a C-demethylated metabolite (M4) was identified, but was only detected in rat liver microsomes; experimental evidence revealed that the C-demethylated metabolite was generated by nonenzymatic decarboxylation of the carboxyl metabolite (M1). Nonenzymatic decarboxylation is postulated to occur due to the resonance stabilization by the oxadiazole ring attached to the tert-butyl moiety.
Keywords: IN-VITRO; DPP-4 INHIBITORS; O-DEALKYLATION; METABOLISM; TERFENADINE